Web-Based Expert Systems For Diagnosing Pest And Disease In Chili Plant Using Forward Chaining - Rusmi, Rusdisal; Defiariany, Defiariany; Purwanti, Sri (Jurnal Sains dan Informatika, 2016)
One of the problems faced by chili farmers is the lack of knowledge about pests and diseases that attack their crops. That requires an expert who can explain about the pests and diseases that attack the chili to the farmers. The limited number of expert would result in farmers having trouble to consult with at any time of their plants attacked by pests and diseases. For that reason, we need a system that has the ability like an expert, where the system provided referral knowledge of pests and disease and its symptoms which are attacking the chili. In this study, a web-based expert system is designed, using a rule base with forward chaining method and the PHP programming language that is intended to help farmers in diagnosing pests and diseases of chili. Diagnosis expert system of pests and diseases in chiliÂ  have been built to help farmers to know quickly the type of pests and diseases that attack the chili plants along with the treatment and the percentage likelihood diagnosed by pests and diseases.